Naegleria fowleri in 2023: A rising threat to Pakistan - Varsha; Dev Kumar; Hersha (Journal of the Pakistan Medical Association, 2024)
Madam, Naegleria fowleri, i.e., brain-eating amoeba, is a single-cell, free-living parasite that resides in soil and warm freshwater bodies such as lakes, rivers, and hot springs. It enters the nasal cavity from contaminated water, uses the olfactory nerve to reach the brain, and causes a deadly infection called primary amoebic meningoencephalitis (PAM), with a mortality rate higher than 97% even with treatment. (1,2) It causes symptoms similar to those of other bacterial and viral meningitis, such as fever, headache, vomiting, altered level of consciousness and coma, followed by death in the span of a week to 10 days. (1) There are 20 strains of Naegleria world worldwide, but only N. fowleri is dangerous to humans. (1) In 2008, the first case was reported from Karachi, Pakistan. (2) By 2019, the number had reached 146, (2) and the cases have been increasing until now. In 2023, eight cases have been reported from May to August, among which seven are from the province of Sindh and one from Punjab. (3, 4, 6) The available data shows that two deaths were due to recreational water activities and others because of contaminated tap water.(3,4) This pathogenic amoeba commonly infects men, and the majority of cases were in people aged 26 to 45 years.(1) Of all the reported cases this year, one was a 32-year-old female, and seven were males in the aged 19-45 years.(3,4, 6) The increasing global warming and higher authorities’ negligence towards WHO recommended chlorination (0.1-10 mg/L) of domestic water supply are contributing factors to the higher burden of Naegleria fowleri cases in Karachi, the largest metropolitan city of Pakistan .(5) The new lethal strain of N. fowleri, named as Karachi-NF001, has been found in one patient who traveled from Saudi Arabia to Karachi in 2019. (2) These emerging cases concern strict actions against this problem and the need to alert the Karachi Water and Sewerage Board (KWSB) regarding consistent chlorination from April to October. (5) The monsoon season (May to September) is the best time to spread awareness regarding its prevention and update the current status of N. fowleri in our country. The general public should be encouraged to use boiled or sterilised water for ablution and avoid aquatic activities in non-chlorinated water during the summer season. (3) Besides that, all underground and overhead water tanks in homes, hospitals, shopping malls, schools, offices, etc. should be cleaned once a year. (3)